Major cardiovascular and neurological events among diabetic patients with severe hypoglycaemia at a tertiary care hospital in Bangladesh (BIRDEM Medical Journal, 2024)
Background: Cardiovascular disease (CVD) is a major cause of death and disability among people with diabetes mellitus (DM). Hypoglycemia is a potential risk factor to augment life threatening CVD. This study intended to find out impact of severe hypoglycemia in adverse cardiovascular and neurological events among patients with DM. Methods: This cross-sectional study was conducted among diabetic patients with severe hypoglycemia (plasma glucose